ALGORITMA K-MEANS UNTUK MELIHAT PENULARAN TERTINGGI VIRUS COVID-19 DISELURUH PROVINSI INDONESIA - Nurahman Nurahman; Diana Dwi Aulia (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2021)
Abstract: The Corona virus or Covid-19 disease began to occur in 2019 until now in 2021. Where the cause of this infectious disease is the Corona Virus. One of the symptoms caused by this viral infection is respiratory problems. The virus in the spread or transmission is classified as very fast. This makes every country, especially Indonesia, where every region has been exposed to Covid-19, which has caused many cases of death, and several impacts, such as the impact on the economy, work, education, and other impacts. With the large spread of the Corona virus in regions or regions in Indonesia, it is necessary to group several parts of Indonesia. Therefore, to make it easier to group a region in Indonesia, in this study a data mining system was used to process large amounts of data by implementing the Clustering Algorithm using the K-Means method. The datasets obtained by researchers without class labels will be processed with the K-Means Algorithm to facilitate data processing to produce the desired goals. The purpose of this research is to see which province has the highest transmission of Covid-19 in Indonesia.